Description of Learning Model Implementation Project Based Learning in the Student Education Research Course of the Electronic Engineering Education Study Program, Faculty of Engineering, Universitas Negeri Makassar - Lu’mu, Lu’mu; Ruslan, Ruslan (Seminar Nasional LP2M UNM, 2024)
Abstract. This study aims to describe the implementation of the learning model Project Based Learning (PjBL) in the teaching and learning process, especially in the educational research methodology course. The method used is a mixed research method (Mixed Methods). The population and sample were 28 undergraduate students of Electronic Engineering Education Study Program. The data analysis technique used descriptive statistics. The results of the study concluded that the results of the study on the implementation of Project Based Learning (PjBL) in the Education research course, it is known that of the nine aspects analyzed, namely the aspects: determining essential questions, active involvement and collaboration, innovation and problem solving, use of 4C skills (communication, collaboration, creativity, critical thinking), project products, presentation of project results, reflection and evaluation of the process, multidisciplinary integration, and aspects of independence and time management, it turns out that in general each aspect is in the high category, namely 80% and above. And there are some aspects that are not in the very low category. For this reason, it is recommended that in the implementation of learning the Educational Research Methodology course, it is better to use the model Project Based Learning (PjBL), so that students can develop their critical and collaborative thinking. Keywords: Project Based Learning, educational research methodology.